Pengembangan Media Diorama Materi Fotosintesis Berbasis Ar Meningkatkan Pemahaman Berfikir Kritis Siswa Dalam Pembelajaran IPAS Kelas IV DI SDN PILANG 1 - Devi Puspita; Ludfi Arya Wardana; Shofia Hattarina; Ribut Prastiwi S (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
This research is motivated by teachers at SD Negeri 1 Probolinggo City who are less innovative in learning methods found that students have difficulty in understanding the concept of photosynthesis because the learning methods used are still conventional, relying only on Student Worksheets (LKS) and lectures causing a lack of active participation of students in the learning process and the low critical thinking skills of students. This study aims to develop Augmented Reality (AR) based diorama learning media on photosynthesis material in IPAS subjects to improve understanding and critical thinking skills of grade IV students at SDN Pilang 1 Probolinggo City. This research aims to develop augmented reality-based diorama media on photosynthesis material. The research method used is Research and Development (R&D) with the ADDIE development model which consists of five stages: Analyze, Design, Develop, Implement, and Evaluate. The results showed that AR-based diorama media was effective in improving students' understanding of the photosynthesis process as well as their critical thinking skills. The validation level measured from the material obtained 90.90% while the media obtained 91.66%. Students become more active in learning, easier to understand abstract concepts, and more capable of analyzing and interesting.